2018
DOI: 10.3390/jcm7110401
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2: A Potential Mediator of the Glycocalyx Injury in Adult Nephrotic Patients

Abstract: Introduction: Glomerulopathy is a group of diseases that affect mainly young adults between the ages of 20 and 40 years. Recently, it has been demonstrated that syndecan-1, a biomarker of endothelial glycocalyx damage, is increased in nephrotic patients with near-normal renal function and it is important to endothelial dysfunction in these patients. Angiopoietin-2 (AGPT2) is an endothelial growth factor that promotes cell derangement. Here we evaluated AGPT2 levels in patients with nephrotic syndrome, near-nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Endothelial dysfunction, resulting from modifications in the composition of the glycocalyx, is a key factor in certain pathologies with a high incidence and may act as a prothrombotic factor 43–47 . In our study, we identified a significant decrease in SDC‐1 within the endothelial lumen compared to extralesional samples.…”
Section: Discussionsupporting
confidence: 48%
“…Endothelial dysfunction, resulting from modifications in the composition of the glycocalyx, is a key factor in certain pathologies with a high incidence and may act as a prothrombotic factor 43–47 . In our study, we identified a significant decrease in SDC‐1 within the endothelial lumen compared to extralesional samples.…”
Section: Discussionsupporting
confidence: 48%
“…Similar to research studies on VEGF, these data are obtained mainly from mouse models [19-21, 23, 27], human EC lines [19, 21, 23, 27], and mouse EC lines [21, 24-26], demonstrating the effects of the Angpt/Tie signal via the transcellular [21] and paracellular [19, 20, 24, 25] pathways. The clinical trial [22] provides evidence of how Angpt2 modulates VP via glycocalyx damage in patients, and more clinical studies are required to add to the reliability of current conclusions.…”
Section: Regulation Of Vpmentioning
confidence: 99%
“…Also, Angpt2 decreases claudin-5 expression in TJs, increases caveolin-1 expression to support the transcellular pathway, and stimulates pericyte detachment and migration to mediate VP [21]. Another possible mechanism of Angpt2-induced VP may involve the damage of the endothelial surface glycocalyx that is important to endothelial dysfunction, as a clinical trial suggests that increased Angpt2 may mediate the association between low-density lipoprotein-cholesterol and glycocalyx injury marked by the biomarker syndecan-1 in patients with DOI: 10.1159/000514314 nephrotic syndrome [22]. Tie1 is less characterized than Tie2, which might directly interact with Tie2 to regulate the Angpt/Tie2 pathway, and its deletion tightens the AJs by upregulating VE-cadherin expression [23].…”
Section: Vegf/vegfr Signalling Pathwaymentioning
confidence: 99%
“…Angiopoietin-2 (ANGPT2) is an endothelial growth factor that promotes cell derangement ( 12 ). Indeed, the linkage between endothelial glycocalyx damage, proteinuria and systemic vascular dysfunction is becoming clearer ( 13 ). Therefore, loss of the endothelial surface layer appears to be a link between albuminuric kidney disease and systemic vascular dysfunction, providing a potential therapeutic target for proteinuric kidney disease.…”
Section: Introductionmentioning
confidence: 99%